REPRESENTATION OF NETIZENS' EMOTIONS THROUGH EXPRESSIVE SPEECH IN YOUTUBE COMMENTS: A PRAGMATIC STUDY OF ISA BAJAJ'S VIDEO ON DEDDY CORBUZIER'S CHANNEL - syadinov surya pratama; Asnawi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of social media has changed people's communication patterns to be more participatory, dialogical, and full of emotional expressions. YouTube, as one of the digital public spaces, provides a comment column that allows netizens to openly express their attitudes, feelings, and judgments towards the content consumed. This study aims to describe and analyze the form and function of expressive speech used by netizens in the comment column of the YouTube video